Kajian Literatur Terhadap Manfaat Keterampilan Kepemimpinan dan Management Penjualan di dalam Perusahaan - Gibson Manalu; Charli Sitinjak (Jurnal Multidisiplin Madani, 2022)
The leadership model is considered by many to be decisive in improving the performance of the sales team in a company. In this case we will discuss in detail the effect of the situational leadership model on improving the performance of the sales team. There are four leadership styles in this model which we will discuss in detail. in our paper. In the end we try to conclude the most effective leadership style that can be used to improve the performance of the sales team in the field. Finding and maintaining good resources in the field of sales leadership and able to work effectively in increasing sales targets is a very difficult task. difficult. Most businesses today are results-oriented; They only make demands to be productive and capable of being a good leader. Failure to consider the nature of sales leadership during the selection process has a great opportunity to present challenges in carrying out sales tasks. In addition, providing development training is also a waste of training given to resources that are not available. not exactly.